Uwe Krüger’s Mainstream (2016): Book Review - Pötzsch, Holger (Nordlit, 2019)
Pötzsch’s book review appears in Norwegian and is thus written for a Scandinavian audience. For a summary of Uwe Krüger’s research in English, see Krüger 2015. For a book review in English, see Keel 2018 (both mentioned in the bibliography). The reviewed book: Uwe Krüger. Mainstream: Warum wir den Medien nicht mehr trauen. ISBN-13: 978–3–406–68851–5. Munich: C. H. Beck, March 2016. Paperback; 174 pages; recommended retail price: €14,95.